THE EFFECT OF CUSTOMER TRUST AND COMPANY IMAGE ON CUSTOMER SATISFACTION AND CUSTOMER LOYALTY IN INDONESIA CLASSIFICATION BUREAU IN SAMARINDA - Syariful Mahsyar; Suharno Suharno; Zainal Abidin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aims to determine the effect of customer trust and company image on customer satisfaction and customer loyalty at the Indonesian Classification Bureau. The population in this study were customers of PT BKI with a total of 95 respondents. The method of data collection is done by giving a list of questions or questionnaires to respondents who are customers at PT BKI, where the questionnaire is distributed to these customers. This study uses a data analysis tool that is partial Least Square (PLS), then this study uses the analysis method of structural equation models or Path Analysis to determine the causal relationship between latent variables contained in structural equations. The tool used in data processing using the Smart PLS program. The results of this study indicate that 1) customer trust has a significant effect on customer satisfaction, 2) company image has a significant effect on customer satisfaction, 3) customer trust has a significant effect on customer loyalty, 4) company image has a significant effect on customer loyalty, 5) customer satisfaction has an significant effect to customer loyalty. Keywords: Customer Trust, Company Image, Customer Satisfaction, Customer Loyalty